Molten Zn-Al-Mg coated steel
By controlling the composition and microstructure of the coating, especially the proportion and distribution of the [Al·Zn mixed microstructure], the problems of insufficient corrosion resistance and coating swelling of molten Zn-Al-Mg coated steel were solved, achieving excellent corrosion resistance and coating stability.
Patent Information
- Application Number
- CN202180040902.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-09
- Filing Date
- 2021-03-19
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-03-19
AI Technical Summary
Existing molten Zn-Al-Mg coated steels have insufficient corrosion resistance on flat surfaces, and the coating is prone to swelling, especially after the coating has formed on the surface.
By controlling the composition and microstructure of the coating, it is ensured that the coating contains 10-70% [Al·Zn mixed microstructure], with the area ratio of the second region being 0-40%, and more than 60% of the nucleation points in the coating thickness direction being located on the steel side. The coating composition contains 1-10% Mg, 4-22% Al, and may contain elements such as Si, Ni, and Ti. The target microstructure is formed by using a specific hot-dip galvanizing method and cooling conditions.
It improves the corrosion resistance of the flat parts of the steel and prevents the coating from swelling after it is formed, thus enhancing the corrosion resistance and adhesion of the coating.
Smart Images

Figure CN115698366B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a molten Zn-Al-Mg based plated steel material.
[0002] This application claims priority based on Japanese Patent Application No. 2020-100073 filed in Japan on June 9, 2020, the contents of which are incorporated herein by reference. Background Art
[0003] In the fields of building materials and civil engineering, molten Zn-Al-Mg-based plated steels are mostly used in an uncoated state. Therefore, molten Zn-Al-Mg-based plated steels having excellent corrosion resistance on the flat surface are required. In addition, recently, molten Zn-Al-Mg-based plated steels are also being used in the fields of home appliances and automobiles. In the fields of home appliances and automobiles, molten Zn-Al-Mg-based plated steels are mostly used in a coated state. In addition, in the field of building materials, the number of scenes in which they are used after coating is also increasing. Therefore, molten Zn-Al-Mg-based plated steels whose coating film is not easily bulged due to corrosion are required. Various molten Zn-Al-Mg-based plated steels are described in Patent Documents 1 to 6.
[0004] Patent document 1 describes a plated steel plate with excellent corrosion resistance, which has a Zn alloy coating on the surface of the steel plate, wherein the Zn alloy coating contains Mg: 1 to 10 wt%, Al: 2 to 19 wt%, Si: 0.01 to 2 wt%, and Mg and Al satisfy the following formula, Mg(%) + Al(%) ≤ 20%, and the remainder contains Zn and unavoidable impurities, wherein the Zn alloy coating has a metal structure in which [Mg2Si phase], [MgZn2 phase] and [Zn phase] are mixed in a matrix of [ternary eutectic structure of Al / Zn / MgZn2].
[0005] Patent document 2 describes a molten Zn-Al-Mg plated steel plate with good corrosion resistance and surface appearance, which is a molten Zn-based plated steel plate with a molten Zn-Al-Mg coating formed on the surface of the steel plate, wherein the molten Zn-Al-Mg coating is Al: 4.0 to 10 weight percent, Mg: 1.0 to 4.0 weight percent, and the remainder contains Zn and unavoidable impurities, and the coating has a metal structure in which [Al phase] is mixed in a matrix of [ternary eutectic structure of Al / Zn / MgZn2].
[0006] Patent document 3 describes a highly corrosion-resistant coated steel sheet with excellent image distinctness, which has a zinc-based coating on one or both sides of the steel sheet, wherein the zinc-based coating contains Al: 4 to 10 mass %, Mg: 1 to 5 mass %, Ti: 0.01 mass % or less, and the remainder contains zinc and unavoidable impurities, as an intermediate layer, a chemical conversion film of a chromate film or a phosphate film, and as an upper layer, an organic coating layer with a thickness of 0.2 to 100 μm.
[0007] Patent document 4 describes a molten Zn-Al-Mg-Si plated steel sheet having a uniform appearance, which has a Zn alloy plated layer, wherein the Zn alloy plated layer contains Mg: 2.8% or more, Al: 10.5% or more, Si: 0.01-0.5%, and the remainder contains Zn and unavoidable impurities, wherein Mg2Zn 11 The X-ray intensity ratio of / MgZn2 is less than 0.5.
[0008] Patent document 5 describes a Zn-AI-Mg based molten-coated steel plate (Zn-AI-Mg based hot-dip coated steel plate), which comprises a steel plate and a hot-dip coated layer, wherein the hot-dip coated layer contains 4 mass % to 22 mass % of Al and 1 mass % to 5 mass % of Mg, and the remainder comprises Zn and unavoidable impurities, wherein the ratio of the X-ray diffraction intensity I(200) of the (200) plane of the Al phase in a cross section of the hot-dip coated layer parallel to the surface of the hot-dip coated layer to the X-ray diffraction intensity I(111) of the (111) plane of the Al phase, i.e., the diffraction intensity ratio I(200) / 1(111) is greater than 0.8.
[0009] Patent document 6 describes a molten Zn-Al-Mg-Si plated steel material with excellent surface properties, which has a coating on the surface of the steel material, wherein the coating is Al: 5 to 18 mass%, Mg: 1 to 10 mass%, Si: 0.01 to 2 mass%, and the remainder contains Zn and unavoidable impurities. 2 There are more than 200 [Al phases].
[0010] However, recently, for molten Zn—Al—Mg-based plated steel materials, there is a demand for further improvement in corrosion resistance of the flat surface portion, and further, there is a strong demand for prevention of swelling of the coating film.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent Application Publication No. 2000-104154
[0014] Patent Document 2: Japanese Patent Application Laid-Open No. 10-226865
[0015] Patent Document 3: Japanese Patent Application Publication No. 2004-225157
[0016] Patent Document 4: Japanese Patent Application Publication No. 2006-193791
[0017] Patent Document 5: International Publication No. 2011 / 001662
[0018] Patent Document 6: Japanese Patent Application Publication No. 2001-355053 Summary of the invention
[0019] Problems to be solved by the invention
[0020] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a molten Zn-Al-Mg-based plated steel material which has excellent corrosion resistance in a flat portion and can prevent swelling of the coating film even when a coating film is formed on the surface of the coating layer.
[0021] Means for solving problems
[0022] In order to solve the above-mentioned problems, the present invention adopts the following configuration.
[0023] [1] A molten Zn-Al-Mg-based plated steel material, comprising: a steel material; and a plating layer formed on a surface of the steel material;
[0024] The above-mentioned plating layer contains Mg: 1-10 mass %, Al: 4-22 mass %, and the remainder contains Zn and impurities in terms of average composition.
[0025] In the above-mentioned coating, in the matrix of the ternary eutectic structure of Al / Zn / MgZn2, 10 to 70% of the area ratio in the cross section of the above-mentioned coating is included in the ternary eutectic structure of Al / Zn / MgZn2.
[0026] The [Al·Zn mixed structure] includes: a first region having a Zn concentration in the range of 75 mass % or more and less than 85 mass %; and a second region located inside the first region and having a Zn concentration in the range of 67 mass % or more and less than 75 mass %,
[0027] The area ratio of the second region in the [Al·Zn mixed structure] in the cross section of the plating layer is more than 0% and is 40% or less.
[0028] [2] The molten Zn-Al-Mg plated steel material according to [1], characterized in that the average composition of the coating layer contains Mg: 1 to 10 mass %, Al: 8 to 22 mass %, and the remainder is Zn and impurities,
[0029] The [Al·Zn mixed structure] includes the first region, the second region, and a third region, wherein the third region is located inside the second region and has a Zn concentration in the range of 55 mass % or more and less than 67 mass %.
[0030] [3] The molten Zn-Al-Mg based plated steel material according to [1] or [2], characterized in that the area ratio of the second region in the [Al·Zn mixed structure] is 5 to 40%.
[0031] [4] The molten Zn-Al-Mg coated steel according to any one of [1] to [3] is characterized in that, when the above-mentioned coating is divided into two equal parts at the 1 / 2 position in the coating thickness direction into the above-mentioned steel side and the coating surface side, 60% or more of the nucleation points of the above-mentioned [Al·Zn mixed structure] in terms of number ratio are present in the area on the steel side of the above-mentioned coating.
[0032] [5] The molten Zn-Al-Mg-based plated steel material according to any one of [1] to [4], characterized in that the coating layer further contains 0.0001 to 2 mass % of Si in terms of average composition.
[0033] [6] The molten Zn-Al-Mg-based plated steel material according to any one of [1] to [5] is characterized in that the above-mentioned coating layer further contains any one or two or more of Ni, Ti, Zr, and Sr in a total amount within a range of 0.0001 to 2 mass % in terms of average composition.
[0034] [7] The molten Zn-Al-Mg-based plated steel material according to any one of [1] to [6] is characterized in that the above-mentioned coating layer further contains any one or more of Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, and Hf in a total amount within a range of 0.0001 to 2 mass % in terms of average composition.
[0035] Effects of the Invention
[0036] According to the present invention, it is possible to provide a molten Zn-Al-Mg-based plated steel material which has excellent corrosion resistance in a flat portion and can prevent swelling of the coating film even when a coating film is formed on the surface of the coating layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a photograph showing a reflected electron image of the plating layer obtained by photographing a cross section of the plating layer of Sample No. 1 using a scanning electron microscope. DETAILED DESCRIPTION
[0038] The molten Zn-Al-Mg plated steel material has a coating layer, wherein the coating layer has the following components: Mg; Al; and the remainder contains Zn and impurities, and as a metal structure, at least one of [MgZn2 phase], [Zn phase], and [Al·Zn mixed structure] is mixed in a matrix of [ternary eutectic structure of Al / Zn / MgZn2]. In addition, when Si is contained in addition to Zn, Al, and Mg in the hot-dip coating layer, it is possible to contain not only the above-mentioned phases and structures but also [Mg2Si phase]. When forming the coating layer, the steel material is immersed in a coating bath containing Mg, Al, and Zn and then the steel material is scooped up, thereby solidifying the molten metal attached to the surface of the steel material. When the coating solidifies, the [Al·Zn mixed structure] crystallizes, and then the matrix of the [ternary eutectic structure of Al / Zn / MgZn2] crystallizes, thereby forming the [Al·Zn mixed structure] in the [ternary eutectic structure of Al / Zn / MgZn2].
[0039] In order to improve the corrosion resistance of the flat part of such molten Zn-Al-Mg plated steel, the inventors of the present invention conducted in-depth research and found out that the [Al·Zn mixed structure] is the starting point of the initial corrosion. The [Al·Zn mixed structure] is a structure derived from the high-temperature Al″ phase (an Al solid solution containing Zn, mostly containing a small amount of Mg) in the ternary equilibrium state diagram of Al-Zn-Mg. According to the state diagram, it is in a state containing fine Zn phase and fine Al phase at room temperature. The structure of this [Al·Zn mixed structure] was studied in detail, and it was found that it can be divided into a first region with a relatively high Zn concentration and a second region with a relatively low Zn concentration. The greater the proportion of the second region, the greater the corrosion resistance of the flat part. The present invention has shown a tendency to decrease. It has also been found that the existence ratio of the second region in the conventional molten Zn-Al-Mg plated steel material has become relatively high. Therefore, it has been recognized that by selecting manufacturing conditions that reduce the existence ratio of the second region, a molten Zn-Al-Mg plated steel material having excellent corrosion resistance in the flat portion can be obtained. In addition, it has been found that by improving the corrosion resistance of the flat portion of the molten Zn-Al-Mg plated steel material, even when a coating film is formed on the coating surface of the molten Zn-Al-Mg plated steel material, it is possible to prevent the coating film from swelling.
[0040] The molten Zn-Al-Mg plated steel material of the present embodiment comprises: a steel material; and a plating layer formed on the surface of the steel material, wherein the plating layer contains Mg: 1 to 10 mass %, Al: 4 to 22 mass %, and the remainder contains Zn and impurities in terms of average composition, wherein in the plating layer, a matrix of a ternary eutectic structure of Al / Zn / MgZn2 contains an [Al·Zn mixed structure] of 10 to 70% in terms of area ratio in a cross section of the plating layer, and the [Al·Zn mixed structure] contains: a first region having a Zn concentration in the range of 75 mass % or more and less than 85 mass %; and a second region, wherein the second region is located inside the first region and has a Zn concentration in the range of 67 mass % or more and less than 75 mass %, and the area ratio of the second region in the [Al·Zn mixed structure] in the cross section of the plating layer is greater than 0% and less than 40%.
[0041] In addition, the molten Zn-Al-Mg-based plated steel material of the present embodiment may include, in the [Al·Zn mixed structure], a first region, a second region and a third region, wherein the third region is located inside the second region and has a Zn concentration in the range of 55 mass % to less than 67 mass %, when the average composition of the coating layer contains Mg: 1 to 10 mass %, Al: 8 to 22 mass %, and the remainder is Zn and impurities.
[0042] Furthermore, the area ratio of the second region in the [Al·Zn mixed structure] may be 5 to 40%.
[0043] Furthermore, when the coating is divided into two equal parts at the 1 / 2 position in the coating thickness direction into the steel side and the coating surface side, it is preferred that 60% or more of the nucleation points of the [Al·Zn mixed structure] are present in the area on the steel side of the coating.
[0044] Hereinafter, the molten Zn—Al—Mg-based plated steel material according to the present embodiment will be described.
[0045] The steel material that serves as the base of the coating is not particularly limited in terms of material. As a material, ordinary steel, Al-killed steel, and some high-alloy steels can be applied, and the shape is not particularly limited. In addition, Ni pre-plating can also be performed on the steel material. The coating of this embodiment is formed by applying the hot dip plating method described later to the steel material.
[0046] Next, the chemical composition of the plating layer will be described.
[0047] The plating layer of the present embodiment contains Mg: 1 to 10 mass %, Al: 4 to 22 mass %, and Zn and impurities as the remainder in terms of average composition. In addition, the plating layer may also contain Si: 0.0001 to 2 mass % in terms of average composition. Furthermore, the plating layer may also contain any one or more of Ni, Ti, Zr, and Sr in a total of 0.0001 to 2 mass % in terms of average composition. Furthermore, the plating layer may also contain any one or more of Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, and Hf in a total of 0.0001 to 2 mass % in terms of average composition.
[0048] The content of Mg is in the range of 1 to 10% by mass based on the average composition. Mg is an element required to improve the corrosion resistance of the coating. When the content of Mg in the coating is less than 1% by mass, the effect of improving the corrosion resistance becomes insufficient. If the content of Mg exceeds 10% by mass, the generation of dross in the plating bath becomes significant, and the adhesion of dross on the coating produces a portion where the coating is not normally formed, so it is possible that the corrosion resistance is reduced. Therefore, the content of Mg is set to 10% by mass or less. From the viewpoint of reduced corrosion resistance caused by the generation of dross, it is preferably set to 1.5 to 6% by mass. It is more preferably set to the range of 2 to 5% by mass.
[0049] The content of Al is in the range of 4 to 22 mass % based on the average composition. Al is an element required to ensure corrosion resistance. When the content of Al in the coating is less than 4 mass %, the effect of improving corrosion resistance becomes insufficient. If it exceeds 22 mass %, although the reason is unknown, the corrosion resistance decreases. From the viewpoint of corrosion resistance, it is preferably set to 8 to 22 mass %. It is more preferably set to 9 to 13 mass %.
[0050] In addition, the coating may also contain Si in the range of 0.0001 to 2 mass %. Si is an effective element for improving the adhesion of the coating. By containing more than 0.0001 mass % of Si, the effect of improving adhesion is shown, so it is preferred to contain more than 0.0001 mass % of Si. On the other hand, even if more than 2 mass % of Si is contained, the effect of improving the adhesion of the coating is also saturated, so the content of Si is set to less than 2 mass %. From the viewpoint of the adhesion of the coating, it may also be set to the range of 0.02 to 1 mass %, or it may be set to the range of 0.03 to 0.8 mass %.
[0051] In addition, the coating may also contain any one or more of Ni, Ti, Zr, and Sr in an average composition of 0.0001 to 2 mass %. The intermetallic compound containing the above-mentioned elements acts as a crystal nucleus (crystal nucleus) of the [Al·Zn mixed structure], making the [ternary eutectic structure of Al / MgZn2 / Zn] finer and more uniform, and improving the appearance and smoothness of the coating. The reason for setting one or more of the above-mentioned elements to a total of 0.0001 to 2 mass % is that when it is less than 0.0001 mass %, the effect of making the solidification structure fine and uniform becomes insufficient. If it exceeds 2 mass %, not only the effect of making the [ternary eutectic structure of Al / Zn / MgZn2] finer is saturated, but also the surface roughness of the coating is increased, thereby deteriorating the appearance. Therefore, the upper limit is set to 2 mass %. In particular, when adding for the purpose of improving the appearance, it is preferably contained in 0.001 to 0.5 mass %. The range of 0.001 to 0.05 mass % is more preferable, and the range of 0.002 to 0.01 mass % is still more preferable.
[0052] The plating layer may contain 0.0001 to 2 mass % of one or more of Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, and Hf in total in an average composition. By containing these elements, the corrosion resistance can be further improved. REM is one or more of the rare earth elements with atomic numbers 57 to 71 in the periodic table.
[0053] The remainder of the coating's chemical composition is zinc and impurities.
[0054] Next, the structure of the coating is described. The coating of the present embodiment includes an [Al·Zn mixed structure] in a matrix of [ternary eutectic structure of Al / Zn / MgZn2] with an area ratio of 10 to 70% relative to the total area of all structures constituting the coating. In addition, in the matrix of [ternary eutectic structure of Al / Zn / MgZn2], in addition to [Al·Zn mixed structure], [MgZn2 phase], [Zn phase], and [Mg2Si phase] may also be included.
[0055] [Ternary eutectic structure of Al / Zn / MgZn2] refers to a ternary eutectic structure of an Al phase, a Zn phase and an intermetallic compound, namely, a MgZn2 phase. The Al phase forming the [ternary eutectic structure of Al / Zn / MgZn2] is, for example, equivalent to the "Al" phase at high temperature in the ternary equilibrium diagram of Al-Zn-Mg (which is an Al solid solution in which a Zn phase is dissolved, and most of them contain a small amount of Mg). This Al" phase at high temperature usually separates into a fine Al main phase and a fine Zn main phase at room temperature. In addition, the Zn phase in the [ternary eutectic structure of Al / Zn / MgZn2] is a Zn solid solution in which a small amount of Al and, depending on the circumstances, a small amount of Mg is further dissolved. The MgZn2 phase in the [ternary eutectic structure of Al / Zn / MgZn2] is an intermetallic compound phase that exists near the Zn of about 84 mass % in the binary equilibrium diagram of Zn-Mg. Just by observing the phase diagram, it can be considered that even if Si and other elements are dissolved in each phase, they are in small amounts and their amounts cannot be clearly distinguished by conventional analysis. Therefore, the ternary eutectic structure formed by these three phases is expressed in this specification as [ternary eutectic structure of Al / Zn / MgZn2].
[0056] Next, the [Al·Zn mixed structure] is described. In the present embodiment, the structure formed by separating the high temperature Al″ phase into a fine Zn main phase and a fine Al main phase during cooling is called [Al·Zn mixed structure]. It should be noted that the Zn main phase may contain Al and Mg in solid solution. The Al main phase may contain Zn and Mg in solid solution.
[0057] [Al·Zn mixed structure] is a phase that has clear boundaries and appears to be an island in the matrix of [ternary eutectic structure of Al / Zn / MgZn2] in the reflected electron image of a scanning electron microscope. It is equivalent to, for example, the "Al" phase at high temperature in the ternary equilibrium diagram of Al-Zn-Mg (an Al solid solution in which a Zn phase is dissolved, containing a small amount of Mg). Regarding this Al" phase at high temperature, the amount of dissolved Zn and Mg varies depending on the Al and Mg concentrations in the plating bath. This high-temperature Al" phase is usually separated into a fine Al main phase and a fine Zn main phase at room temperature, but the island shape seen at room temperature can be regarded as retaining the shape of the Al" phase at high temperature. Only by observing the state diagram, it can be considered that Si and other added elements are not dissolved in this phase, or even if Si and other added elements are dissolved, they are extremely small, but they cannot be clearly distinguished by conventional analysis. Therefore, this structure derived from the Al" phase at high temperature and retaining the shape of the Al" phase is referred to as "Al·Zn mixed structure" in this specification. This "Al·Zn mixed structure" can be clearly distinguished from the Al phase that forms the "ternary eutectic structure of Al / Zn / MgZn2" in the reflected electron image of a scanning electron microscope.
[0058] The area ratio of the [Al·Zn mixed structure] in the cross section of the plating layer is preferably in the range of 10 to 70%. When the area ratio of the [Al·Zn mixed structure] is in this range, the corrosion resistance of the flat surface portion can be improved.
[0059] The method for determining the area ratio is to observe the cross-section of the coating through the reflected electron image of a scanning electron microscope. Take photos of 5 locations at a magnification of 1000 times. The photos are taken in a manner that allows the entire thickness of the coating to enter the field of view. The photo shooting position is randomly selected. The calculation result of the area ratio must be accepted and the shooting position must be selected arbitrarily. Furthermore, the energy dispersive X-ray elemental analysis device attached to the scanning electron microscope is used to obtain the element mapping data corresponding to the photographed photo to determine the [Al·Zn mixed structure]. Then, the total cross-sectional area of the [Al·Zn mixed structure] appearing in all the cross-sectional photos is measured, and the area ratio of the [Al·Zn mixed structure] is determined by dividing it by the cross-sectional area of the coating appearing in all the cross-sectional photos.
[0060] In addition, the [Zn phase] refers to a phase that has a clear boundary and appears to be an island in the matrix of the [ternary eutectic structure of Al / Zn / MgZn2]. In fact, a small amount of Al and a small amount of Mg are sometimes dissolved. It can be considered that Si and other additive elements are not dissolved in this phase only by observing the state diagram, or even if Si and other additive elements are dissolved, they are extremely small. The [Zn phase] can be clearly distinguished from the Zn phase that forms the [ternary eutectic structure of Al / Zn / MgZn2] in the reflected electron image of a scanning electron microscope. In the coating of this embodiment, the [Zn phase] may also be included depending on the manufacturing conditions, but the effect on the improvement of the corrosion resistance of the planar portion is basically not observed in the experiment, so even if the [Zn phase] is included in the coating, there is no special problem.
[0061] In addition, [MgZn2 phase] refers to a phase that has a clear boundary and appears to be an island in the matrix of [ternary eutectic structure of Al / Zn / MgZn2], but in fact, a small amount of Al is sometimes dispersed and dissolved. It can be considered that Si and other additive elements are not dissolved in this phase only by observing the state diagram, or even if Si and other additive elements are dissolved, they are extremely small. This [MgZn2 phase] can be clearly distinguished from the MgZn2 phase that forms the [ternary eutectic structure of Al / Zn / MgZn2] in the reflected electron image of a scanning electron microscope. In the coating of this embodiment, the [MgZn2 phase] may not be contained depending on the manufacturing conditions, but it is included in the coating under most manufacturing conditions.
[0062] In addition, [Mg2Si phase] refers to a phase that has a clear boundary and appears to be an island in the solidified structure of the Si-containing coating. It can be considered that Zn, Al, and other additive elements are not dissolved in the coating, or even if Zn, Al, and other additive elements are dissolved in the coating, they are extremely small. This [Mg2Si phase] can be clearly distinguished in the reflected electron image of a scanning electron microscope in the coating.
[0063] Next, the fine structure of the [Al·Zn mixed structure] is described. As described above, the [Al·Zn mixed structure] shows an island shape that retains the shape of the Al" phase at high temperature. In addition, the internal structure of the [Al·Zn mixed structure] can be inferred from the state diagram to show a morphology separated into a fine Al phase and a fine Zn phase at room temperature.
[0064] On the other hand, if the distribution of Zn concentration of [Al·Zn mixed structure] is observed, [Al·Zn mixed structure] can be divided into at least a first region and a second region, wherein the second region is located inside the first region and has an average Zn concentration lower than that of the first region. In addition, when the average Al concentration of the coating is 8 to 22 mass %, a third region having an average Zn concentration lower than that of the second region is included inside the second region. The first region is located at the outermost side of [Al·Zn mixed structure] when the coating is observed in cross section, and constitutes a boundary with [ternary eutectic structure of Al / Zn / MgZn2]. The second region is located inside the first region, and the third region is located further inside the second region.
[0065] The first region is a region where the Zn concentration is 75 mass % or more and less than 85 mass %, the second region is a region where the Zn concentration is 67 mass % or more and less than 75 mass %, and the third region is a region where the Zn concentration is 55 mass % or more and less than 67 mass %. The remainder other than Zn is Al and impurities. In addition, when the plating layer contains Si, Si may be contained in any one or all of the first region, the second region, and the third region.
[0066] The proportion of the second region in the [Al·Zn mixed structure] needs to be in the range of more than 0% and less than 40% relative to the [Al·Zn mixed structure] in terms of the area ratio when the coating is observed in cross section. The proportion of the second region can be in the range of 5 to 40%, or more than 5% and less than 40%, or in the range of 5 to 35%. The less the proportion of the second region in the [Al·Zn mixed structure], the higher the corrosion resistance of the flat portion. However, setting the area ratio of the second region to 0% is accompanied by difficulties in manufacturing, so the lower limit is set to more than 0%. In addition, if the second region exceeds 40%, the corrosion resistance of the flat portion decreases, so the upper limit is set to less than 40%. It was confirmed that if corrosion begins, the second region in the [Al·Zn mixed structure] of the coating, especially the second region with a Zn concentration of more than 67 mass % and less than 75 mass %, is preferentially corroded. Therefore, it is inferred that the corrosion resistance of the flat portion is improved by reducing the second region that becomes the starting point of corrosion.
[0067] In addition, the area ratios of the first region and the third region do not need to be particularly limited.
[0068] The method for determining the fine structure of the [Al·Zn mixed structure] is described. The method for determining the fine structure of the [Al·Zn mixed structure] is to use the element mapping data of the photograph used in the determination of the area ratio of the [Al·Zn mixed structure]. First, the distribution of the Zn concentration inside the [Al·Zn mixed structure] is analyzed. During the analysis, an energy dispersive X-ray elemental analysis device attached to a scanning electron microscope (SEM) is used, and the acceleration voltage of the SEM is set to 15kV. In this case, according to the relationship with the escape depth of the characteristic X-ray, the Zn concentration is actually for every approximately 1μm 2 By mapping it, component analysis can be performed with a grid of about 1 μm. The ranges of the first region, the second region, and the third region are determined based on the Zn concentration (mass %) obtained from the component analysis results.
[0069] Specifically, according to the component analysis results, the region in which the Zn concentration is in the range of 75 mass % or more and less than 85 mass % is determined as the first region, the region in which the Zn concentration is in the range of 67 mass % or more and less than 75 mass % is determined as the second region, and the region in which the Zn concentration is in the range of 55 mass % or more and less than 67 mass % is determined as the third region. Then, the cross-sectional area of each region is measured. The above measurement is performed on all the [Al·Zn mixed structures] appearing in all the photographs, and the total area of the second region in all the [Al·Zn mixed structures] is measured. Then, the area ratio of the second region is determined by dividing the total area of the second region by the [total cross-sectional area of the Al·Zn mixed structure] as the measurement object.
[0070] The molten Zn-Al-Mg plated steel of the present embodiment is formed as described below by immersing the steel in a plating bath and then scooping up the steel, thereby solidifying the molten metal attached to the surface of the steel. As described above, when the coating solidifies, the [Al·Zn mixed structure] first crystallizes, and then the matrix of the [ternary eutectic structure of Al / Zn / MgZn2] crystallizes. The first crystallized [Al·Zn mixed structure] originates from the high-temperature Al" phase in the ternary equilibrium state diagram of Al-Zn-Mg, and the high-temperature Al" phase eventually becomes the [Al·Zn mixed structure] in the present embodiment. In the [Al·Zn mixed structure], first, the nucleation point generated in the molten metal becomes the starting point, the primary arm grows from the nucleation point, and then the secondary arm is generated from the primary arm. Therefore, the [Al·Zn mixed structure] becomes a dendritic structure with the nucleation point as the starting point.
[0071] Moreover, in the case of the molten Zn-Al-Mg plated steel material of the present embodiment, when the coating is divided into two equal parts at the 1 / 2 position in the coating thickness direction into the steel material side and the coating surface side, it is preferred that 60% or more of the nucleation points of the [Al·Zn mixed structure] are present in the region on the steel material side of the coating. As a result, among the constituent structures of the coating, the [Al·Zn mixed structure] that becomes the starting point of the initial corrosion becomes present in large quantities in the region on the steel material side, and the presence ratio of the [Al·Zn mixed structure] in the region on the surface side of the coating decreases. As a result, the corrosion resistance of the flat portion of the coating is further improved.
[0072] In addition, when a coating film is formed on the plated layer, the [Al·Zn mixed structure] may become a factor that hinders the adhesion between the plated layer and the coating film. Since a large amount of [Al·Zn mixed structure] exists in the area on the steel plate side of the plated layer, the proportion of [Al·Zn mixed structure] exposed on the surface is relatively reduced, thereby further improving the effect of preventing the coating film from swelling when a coating film is formed on the surface of the plated layer.
[0073] The method for determining the distribution of nucleation points of the [Al·Zn mixed structure] is set as follows. First, the thickness of the coating is determined by observing the cross section of the coating. Then, on the surface of the coating, a square area with a side of 1 mm is set as the measurement area. Then, the coating in the measurement area is slowly ground from the surface, and the newly appeared ground surface is observed by an electron microscope. Specifically, when the total thickness of the coating is set to t, the positions t / 4, t / 2, and 3t / 4 are exposed in sequence in the depth direction from the coating surface by grinding, and the morphology of the [Al·Zn mixed structure] is confirmed at any time by an electron microscope on each ground surface. The depth of grinding is controlled by observing the shape changes of the indentation given in advance.
[0074] The nucleation point in the [Al·Zn mixed structure] is the junction point of the primary arms of the [Al·Zn mixed structure]. On the grinding surface far from the [nucleation point of the Al·Zn mixed structure], the primary arms appear to be discretely arranged, but on the grinding surface close to the nucleation point, 4 or 6 primary arms appear to be close. Therefore, when observing each grinding surface, the change in the shape of the primary arms in each grinding surface is used to infer whether the nucleation point is located on the steel side of the grinding surface under observation or on the surface side of the coating. By operating in this way, in the grinding surfaces at the t / 4 position, t / 2 position, and 3t / 4 position in the depth direction from the coating surface, by confirming the morphology of the [Al·Zn mixed structure] at any time, it is possible to confirm whether the nucleation point is located closer to the steel side than the t / 2 position or on the coating surface side. Then, the ratio of the number of nucleation points located on the steel material side of the t / 2 position to the total number of nucleation points of the [Al·Zn mixed structure] observed in the measurement area is calculated. The above method is applied to a total of 5 measurement areas, and the average of the obtained values is taken as the ratio of the number of nucleation points located on the steel material side of the t / 2 position of the coating layer.
[0075] The coating weight is preferably 10 to 300 g / m 2 The range can also be 20 to 250 g / m 2 If the amount of the coating is small, the corrosion resistance cannot be fully ensured. In addition, if the amount of the coating is too thick, cracks may occur in the coating when it is processed into a component shape, etc.
[0076] Next, the manufacturing method of the molten Zn-Al-Mg plated steel material of the present embodiment is described. The molten Zn-Al-Mg plated steel material of the present embodiment is formed by the so-called hot dip coating method described below: a coating bath is attached to the surface of the steel material, and then the steel material is scooped out of the coating bath to solidify the molten metal attached to the surface of the steel material.
[0077] The composition of the plating bath preferably contains Mg: 1 to 10 mass %, Al: 4 to 22 mass %, and Zn and impurities as the remainder. In addition, the plating bath may contain Si: 0.0001 to 2 mass %. Furthermore, the plating bath may contain any one or more of Ni, Ti, Zr, and Sr in a total of 0.0001 to 2 mass %. Furthermore, the plating bath may contain any one or more of Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, and Hf in a total of 0.0001 to 2 mass %.
[0078] The temperature of the plating bath is preferably in the range of more than 380°C and 600°C or less, and may be in the range of 400 to 600°C.
[0079] Before being immersed in the plating bath, the steel material is preferably subjected to a surface reduction treatment by heating in a reducing atmosphere. For example, a heat treatment is performed at a temperature of 600°C or above, preferably 750°C or above, for more than 30 seconds in a mixed atmosphere of nitrogen and hydrogen. After the reduction treatment, the steel material is cooled to the temperature of the plating bath and then immersed in the plating bath. The immersion time can be, for example, more than 1 second. When the steel material immersed in the plating bath is scooped up, the amount of coating adhesion is adjusted by gas wiping. The adhesion amount is preferably 10 to 300 g / m as described above. 2 The range can also be 20 to 250 g / m 2 range.
[0080] In the method for producing a molten Zn-Al-Mg-based plated steel material of the present embodiment, the cooling conditions after scooping out from the coating bath are important. There are the following two types of cooling conditions, and either condition may be adopted.
[0081] The cooling conditions after being taken out of the plating bath until the temperature reaches 365 to 380° C. are not particularly limited, and may be ordinary cooling conditions of about 5 to 10° C. / sec.
[0082] The first cooling condition is set to the following conditions: after the steel material is scooped out of the coating bath, it is maintained at a constant temperature in the temperature range of 365 to 380°C where the coating is not completely solidified before reaching the top roll, and then rapidly cooled from 365°C. The temperature here is the surface temperature of the molten metal (coating). The holding time when the temperature is maintained at a constant temperature in the temperature range of 365 to 380°C is preferably in the range of 10 to 300 seconds. In addition, the average cooling rate when rapidly cooled after constant holding at 365 to 380°C is preferably in the range of 50 to 100°C / second. Regarding rapid cooling, it is preferable to perform rapid cooling immediately after the temperature holding time ends. In addition, it is preferable to perform rapid cooling until the temperature of the coating reaches below 100°C. By performing the above-mentioned holding and rapid cooling, the target structure can be obtained. The reason for maintaining the temperature in the range of 365 to 380°C is that the growth of the high-temperature Al" phase formed at this temperature by the solid-liquid interface reaction is promoted by the liquid phase remaining in an unsolidified state during the coating. In the fully solidified state, the element migration between the structures is not promoted, and the high-temperature Al" phase does not grow, so the target structure cannot be obtained. The reason for rapid cooling from 365°C is to suppress the formation of the high-temperature Al" phase in the second region that becomes the [Al·Zn mixed structure]. It should be noted that when the coating is reheated after it is completely solidified and maintained in the temperature range of 365 to 380°C, the Mg2Zn11 phase that deteriorates the corrosion resistance may be formed, which is not preferred. In addition, when the Mg content in the coating is less than 1% by mass, in the temperature range of 365 to 380°C, the ratio of the liquid phase remaining in an unsolidified state during the coating is small, so the growth of the high-temperature Al" phase cannot be promoted, and the target structure cannot be obtained. From the viewpoint of promoting the growth of the high-temperature Al" phase, the Mg content in the coating is preferably 1.5% by mass or more.
[0083] The second cooling condition is set to the following conditions: after the steel is scooped out of the coating bath, it is slowly cooled between 380°C and 365°C before reaching the top roll where the coating is not completely solidified, and then rapidly cooled. The temperature here is the surface temperature of the molten metal (coating). The average cooling rate in the case of slow cooling in the temperature range from 380°C to 365°C is preferably in the range of 0.1 to 0.4°C / second. In addition, the average cooling rate in the case of rapid cooling after slow cooling is preferably in the range of 50 to 100°C / second. Regarding rapid cooling, it is preferable to perform rapid cooling immediately after the end of slow cooling. In addition, it is preferable to perform rapid cooling until the temperature of the coating reaches below 100°C.
[0084] If the cooling conditions described above are deviated from, it will be impossible to set the area ratio of the second region to a range exceeding 0% and not more than 40%.
[0085] As described above, the molten Zn—Al—Mg-based plated steel material of the present embodiment can be produced.
[0086] The flat portion of the molten Zn—Al—Mg-based plated steel material of the present embodiment is excellent in corrosion resistance, and even when a coating film is formed on the surface of the plated layer, swelling of the coating film can be prevented.
[0087] Example
[0088] After degreasing, the SPCC (JIS G3141) with a thickness of 0.8 mm was subjected to a heat reduction treatment at 800°C for 60 seconds in a N2-H2 atmosphere using a hot dip plating simulator manufactured by Toei Co., Ltd. After cooling to the plating bath temperature, it was immersed in a 450°C plating bath with the same composition as the average composition of the plating layer shown in Table 1 for 3 seconds, and then the plating layer adhesion was set to 135 g / m on a single side by N2 wiping. 2 .
[0089] The control of the [Al·Zn mixed structure] is carried out by controlling the cooling after plating, and the target structure is produced in the following manner: the coating is held or retained for 10 to 300 seconds between 380 and 365°C before reaching the top roll, where the coating is not completely solidified, and then rapidly cooled to below 100°C at an average cooling rate of 50 to 100°C / second. Inventive Examples 47 to 52 are performed by slow cooling between 380 and 365°C for 40 to 150 seconds (the average cooling rate during slow cooling is in the range of 0.1 to 0.4°C / second) and then rapidly cooled to below 100°C. Other inventive examples are performed by only holding at 375°C for the holding time shown in Table 1 and then rapidly cooled to below 100°C. Comparative Example 5 does not perform holding or slow cooling between 380 and 365°C. As an example of a cross-sectional SEM image of a prepared sample, a cross-sectional photograph of the coating of No. 1 is shown. Figure 1 The results are shown in Table 1A, Table 1B, Table 2A, and Table 2B.
[0090] Table 1A and Table 1B show the cooling conditions after coating and the average composition of the coating. Table 2A and Table 2B show the area ratio of the [Al·Zn mixed structure] in the cross section of the coating, the area ratio of the second region in the [Al·Zn mixed structure], the average Zn concentration of the first region, the second region and the third region, and the position of the nucleation point of the [Al·Zn mixed structure]. In addition, the evaluation results of the flat corrosion resistance and the corrosion resistance after coating are shown.
[0091] The average composition of the plating layer is measured by peeling and dissolving the plating layer and then analyzing the content of elements contained in the plating layer by inductively coupled plasma emission spectrometry.
[0092] The area ratio of the [Al·Zn mixed structure] in the coating is obtained by taking reflected electron images of 5 parts of the cross section of the coating at a magnification of 1000 times using a scanning electron microscope. The photographs are taken in such a way that the entire thickness of the coating is within the field of view. The photo shooting position is randomly selected. Furthermore, the energy dispersive X-ray elemental analysis device attached to the scanning electron microscope is used to obtain the element mapping data corresponding to the photographed photos to determine the [Al·Zn mixed structure]. Then, the total cross-sectional area of the [Al·Zn mixed structure] appearing in all the cross-sectional photos is measured, and the area ratio of the [Al·Zn mixed structure] is determined by dividing it by the cross-sectional area of the coating appearing in all the cross-sectional photos.
[0093] The area ratio of the second region in the [Al·Zn mixed structure] and the average Zn concentrations of the first region, the second region, and the third region were measured as follows.
[0094] The cross section of the coating was magnified to 1000 times using a scanning electron microscope to take reflected electron images of 5 locations. The photographs were taken in such a way that the entire thickness of the coating was within the field of view. The photographing positions were randomly selected. Furthermore, an energy dispersive X-ray elemental analyzer attached to the scanning electron microscope was used to obtain elemental mapping data corresponding to the photographs taken, and the [Al·Zn mixed structure] was determined. The acceleration voltage of the SEM was set to 15 kV when obtaining the elemental mapping data. In this case, each approximately 1 μm 2 The Zn concentration in the region can be measured, and the component analysis can be performed with a grid of about 1 μm. The ranges of the first region, the second region, and the third region are determined based on the Zn concentration (mass %) obtained from the component analysis results of the element mapping data.
[0095] Specifically, the region in which the Zn concentration is 75 mass % or more and less than 85 mass % is determined as the first region, the region in which the Zn concentration is 67 mass % or more and less than 75 mass % is determined as the second region, and the region in which the Zn concentration is 55 mass % or more and less than 67 mass % is determined as the third region. Then, the cross-sectional area of each region is measured. The above measurement is performed on all the [Al·Zn mixed structures] appearing in all the photographs, and the total area of the second region in all the [Al·Zn mixed structures] is measured. Then, the area ratio of the second region is determined by dividing the total area of the second region by the total cross-sectional area of the [Al·Zn mixed structure] to be measured.
[0096] Furthermore, the average concentration of Zn in each region was determined from the measurement results of the Zn concentration in the first region, the second region, and the third region.
[0097] The determination method of the distribution of nucleation points of the [Al·Zn mixed structure] is set as follows. First, the thickness of the coating is determined by observing the cross section of the coating. Then, on the surface of the coating, a square area with a side of 1 mm is set as the measurement area. Then, the coating in the measurement area is slowly ground from the surface, and the newly appeared grinding surface is observed by an electron microscope. Specifically, when the total thickness of the coating is set to t, the grinding surfaces are exposed in sequence at the positions t / 4, t / 2, and 3t / 4 in the depth direction from the coating surface, and the morphology of the Al·Zn mixed structure is confirmed at any time by an electron microscope on each grinding surface. The depth of grinding is controlled by observing the shape changes of the indentation given in advance.
[0098] The nucleation point in the [Al·Zn mixed structure] is the junction point of the primary arms of the [Al·Zn mixed structure]. On the grinding surface far from the nucleation point of the [Al·Zn mixed structure], the primary arms appear to be discretely arranged, but on the grinding surface close to the nucleation point, 4 or 6 primary arms appear to be close. Therefore, when observing each grinding surface, the change in the shape of the primary arms in each grinding surface is used to infer whether the nucleation point is located on the steel side of the observed grinding surface or on the surface side of the coating. In this way, in the grinding surface at the t / 4 position, t / 2 position and 3t / 4 position in the depth direction from the coating surface, by confirming the morphology of the [Al·Zn mixed structure] at any time, it is confirmed whether the nucleation point is located closer to the steel side than the t / 2 position or on the coating surface side. Then, the ratio of the number of nucleation points located on the steel material side of the t / 2 position to the total number of nucleation points of the [Al·Zn mixed structure] observed in the measurement area is calculated. The above method is applied to a total of 5 measurement areas, and the average of the obtained values is taken as the ratio of the number of nucleation points located on the steel material side of the t / 2 position of the coating layer.
[0099] In Tables 2A and 2B, a column for the position of the nucleation points of the [Al·Zn mixed structure] is set. When the coating is divided into two equal parts at the 1 / 2 position in the coating thickness direction into the steel side and the coating surface side, the case where 60% or more of the nucleation points of the [Al·Zn mixed structure] in terms of number ratio exist in the area on the steel side of the coating is set as ○, and the case where this is not the case is set as ×.
[0100] The obtained alloy plated steel sheet was cut into 100 mm × 50 mm and subjected to a flat corrosion resistance evaluation test. The flat corrosion resistance was evaluated by the corrosion promotion test specified in JASO-CCT-M609 and by comparing the corrosion loss after 120 cycles. The evaluation criteria were set as follows, with ◎, ○, and △ as qualified.
[0101] ◎: Corrosion loss less than 40g / m 2
[0102] ○: Corrosion loss is 40g / m 2 Above and below 60g / m 2
[0103] △: Corrosion loss is 60g / m 2 Above and below 80g / m 2
[0104] ×: Corrosion loss is 80g / m 2 above
[0105] The corrosion resistance after coating (the swelling of the coating after coating) was evaluated by forming a chemical conversion treatment layer with a film thickness of 1.2 μm on a flat test piece, and after forming a coating layer with a film thickness of 20 μm, a cut was given to the front side with a cutter knife to reach the base metal, and 120 cycles of SST 4 hours → drying 2 hours → wetting 2 hours were performed as one cycle of CCT. The maximum swelling width on one side of the cut after the test was completed was used for evaluation.
[0106] <Chemical conversion treatment layer>
[0107] The chemical conversion film is formed by applying a chromate-free chemical conversion solution prepared by mixing a silane coupling agent, tannic acid, silica, and a polyester resin on the plated layer and drying the mixture.
[0108] <Coating layer>
[0109] The coating layer was formed by applying the primer resin and the topcoat resin described below on the chemical conversion treatment film. The thickness of the layer formed by the primer resin was set to 5 μm, and the thickness of the layer formed by the topcoat resin was set to 15 μm, and the total thickness was set to 20 μm.
[0110] <Film-forming components of coating layer>
[0111] (1) Primer coating resin for front and back surfaces
[0112] Polyester / melamine + isocyanate combined curing type (FLC687 coating resin manufactured by Nippon Fine Coatings)
[0113] (2) Front outer coating resin
[0114] High molecular weight polyester / melamine curing type (FLC7000 coating resin manufactured by Nippon Fine Coatings)
[0115] (3) Back side outer coating resin
[0116] Polyester / melamine curing type (FLC100HQ coating resin manufactured by Nippon Fine Coatings)
[0117] The following are the evaluation criteria for corrosion resistance after painting. The evaluation was performed using the following scoring system. ◎, ○, and △ were considered acceptable.
[0118] ◎: Maximum bulging width less than 5mm
[0119] ○: Maximum bulge width is 5mm or more and less than 8mm
[0120] △: Maximum bulge width is 8mm or more and less than 10mm
[0121] ×: Maximum bulging width is 10 mm or more
[0122] [Table 1A]
[0123]
[0124] The underlined characters indicate outside the scope of the present invention.
[0125] [Table 1B]
[0126]
[0127] The underlined characters indicate outside the scope of the present invention.
[0128] [Table 2A]
[0129]
[0130] The underlined characters indicate outside the scope of the present invention.
[0131] [Table 2B]
[0132]
[0133] The underlined characters indicate outside the scope of the present invention.
[0134] like Figure 1 As shown in , the plating layer of Invention Example No. 1 contains [Al·Zn mixed structure] in the matrix of [ternary eutectic structure of Al / Zn / MgZn2].
[0135] Similarly, the plating layers of Inventive Examples No. 2 to 52 and Comparative Examples No. 1 to 5 contain an [Al·Zn mixed structure] in a matrix of [ternary eutectic structure of Al / Zn / MgZn2].
[0136] As shown in Table 1A, Table 1B, Table 2A and Table 2B, the molten Zn-Al-Mg plated steel materials of No. 1 to 52 of the inventive examples all meet the scope of the present invention, and have good flat corrosion resistance and corrosion resistance after painting. In addition, as shown in Table 2, the flat corrosion resistance and coating corrosion resistance of the molten Zn-Al-Mg plated steel materials whose positions of the nucleation points of the [Al·Zn mixed structure] are evaluated as "○" are more excellent.
[0137] On the other hand, the Al content of the coating layer of the molten Zn-Al-Mg-based plated steel material of Comparative Example No. 1 is low, the area ratio of the [Al·Zn mixed structure] in the coating layer is low, and the [Al·Zn mixed structure] does not contain the second region. Therefore, the flat corrosion resistance and the corrosion resistance after painting become inferior.
[0138] The Al content of the coating layer of the molten Zn-Al-Mg-based plated steel of Comparative Example No. 2 is excessive, the area ratio of the [Al·Zn mixed structure] in the coating layer is high, and the area ratio of the second region in the [Al·Zn mixed structure] also becomes high, resulting in poor plane corrosion resistance and corrosion resistance after painting.
[0139] The molten Zn-Al-Mg plated steel material of Comparative Example No. 3 does not contain Mg in the plating layer, and the area ratio of the second region in the [Al·Zn mixed structure] is also increased, and the flat corrosion resistance and the corrosion resistance after coating are inferior.
[0140] The molten Zn-Al-Mg plated steel material of Comparative Example No. 4 has an excessive Mg content in the plating layer and a high area ratio of the second region in the [Al·Zn mixed structure], resulting in poor flat corrosion resistance and post-painting corrosion resistance.
[0141] Since the molten Zn-Al-Mg plated steel material of Comparative Example No. 5 was not held at 380 to 365°C or slowly cooled, the area ratio of the second region in the [Al·Zn mixed structure] became high, and the flat corrosion resistance and the corrosion resistance after coating became inferior.
Claims
1. A molten Zn-Al-Mg coated steel material, characterized in that: The invention comprises: a steel material; and a plating layer formed on the surface of the steel material. The plating layer contains Mg: 1-10 mass %, Al: 4-22 mass %, and the remainder is Zn and impurities in terms of average composition. In the coating, the matrix of the ternary eutectic structure of Al / Zn / MgZn2 contains an Al·Zn mixed structure with an area ratio of 10 to 70% in the cross section of the coating, The Al·Zn mixed structure is an island-shaped structure that retains the shape of the Al″ phase at high temperature. The Al·Zn mixed structure includes: a first region having a Zn concentration in a range of 75 mass % or more and less than 85 mass %; and a second region located inside the first region and having a Zn concentration in a range of 67 mass % or more and less than 75 mass %, The area ratio of the second region in the Al·Zn mixed structure in the cross section of the plating layer is more than 0% and is 40% or less.
2. The molten Zn-Al-Mg based plated steel material according to claim 1, characterized in that: The average composition of the plating layer contains Mg: 1-10 mass %, Al: 8-22 mass %, and the remainder is Zn and impurities. The Al·Zn mixed structure includes the first region, the second region, and a third region. The third region is located inside the second region and has a Zn concentration in a range of 55 mass % or more and less than 67 mass %.
3. The molten Zn-Al-Mg based plated steel material according to claim 1 or claim 2, characterized in that: The area ratio of the second region in the Al·Zn mixed structure is 5 to 40%.
4. The molten Zn-Al-Mg based plated steel material according to claim 1 or claim 2, characterized in that: When the coating is divided into two equal parts at the 1 / 2 position in the coating thickness direction into the steel material side and the coating surface side, 60% or more of the nucleation points of the Al·Zn mixed structure are present in the area on the steel material side of the coating.
5. The molten Zn-Al-Mg based plated steel material according to claim 1 or claim 2, characterized in that: The plating layer further contains 0.0001 to 2 mass % of Si in terms of average composition.
6. The molten Zn-Al-Mg based plated steel material according to claim 5, characterized in that: The plating layer further contains any one or two or more of Ni, Ti, Zr, and Sr in a total amount within a range of 0.0001 to 2 mass % in terms of average composition.
7. The molten Zn-Al-Mg based plated steel material according to claim 5, characterized in that: The coating further contains any one or two or more of Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, and Hf in an average composition within a total range of 0.0001 to 2 mass %, wherein the REM is one or two or more rare earth elements with atomic numbers 57 to 71 in the periodic table.
8. The molten Zn-Al-Mg based plated steel material according to claim 6, characterized in that: The coating further contains any one or two or more of Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, and Hf in an average composition within a total range of 0.0001 to 2 mass %, wherein the REM is one or two or more rare earth elements with atomic numbers 57 to 71 in the periodic table.
Citation Information
Patent Citations
Hot dip zinc-aluminum-magnesium plated steel sheet good in corrosion resistance and surface appearance and its production
JP1998226865A
Plated steel sheet and coated steel sheet excellent in corrosion resistance and production of the same
JP2000104154A
Hot dip zn-al-mg-si plated steel excellent in surface property and its production method
JP2001355053A
Highly corrosion-resistant coated steel plate having excellent sharpness
JP2004225157A
HOT-DIP Zn-Al-Mg-Si-PLATED STEEL SHEET SUPERIOR IN SURFACE APPEARANCE, AND MANUFACTURING METHOD THEREFOR
JP2006193791A